2012
DOI: 10.1242/dev.074831
|View full text |Cite
|
Sign up to set email alerts
|

The cyclophilin DIAGEOTROPICA has a conserved role in auxin signaling

Abstract: SUMMARYAuxin has a fundamental role throughout the life cycle of land plants. Previous studies showed that the tomato cyclophilin DIAGEOTROPICA (DGT) promotes auxin response, but its specific role in auxin signaling remains unknown. We sequenced candidate genes in auxin-insensitive mutants of Physcomitrella patens and identified mutations in highly conserved regions of the moss ortholog of tomato DGT. As P. patens and tomato diverged from a common ancestor more than 500 million years ago, this result suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 53 publications
(67 reference statements)
1
46
0
Order By: Relevance
“…Considering that the key components, including LRT2-like proteins and Aux/IAAs, are highly conserved in both lower and higher plants and that the loss-of-function mutations in tomato DGT and moss PpDGT cause a similar auxin-insensitive phenotype 29,30 , the cyclophilin-catalysed isomerization of the Aux/IAA transcriptional repressors may represent a general mechanism in regulating auxin signalling in the plant kingdom. In agreement with this notion, LRT2/OsCYP2 was found to directly interact with OsSGT1 (suppressor of G2 allele of skp1) 17 , whose Arabidopsis homologous gene AtSGT1b was identified from a genetic screen for the enhancers of tir1-1 and was characterized as co-chaperone to be required for the SCF TIR1 -mediated degradation of Aux/IAA proteins 39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that the key components, including LRT2-like proteins and Aux/IAAs, are highly conserved in both lower and higher plants and that the loss-of-function mutations in tomato DGT and moss PpDGT cause a similar auxin-insensitive phenotype 29,30 , the cyclophilin-catalysed isomerization of the Aux/IAA transcriptional repressors may represent a general mechanism in regulating auxin signalling in the plant kingdom. In agreement with this notion, LRT2/OsCYP2 was found to directly interact with OsSGT1 (suppressor of G2 allele of skp1) 17 , whose Arabidopsis homologous gene AtSGT1b was identified from a genetic screen for the enhancers of tir1-1 and was characterized as co-chaperone to be required for the SCF TIR1 -mediated degradation of Aux/IAA proteins 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Gly 72 is a highly conserved residue located in the PPIase domain ( Supplementary Fig. 6a) and mutations in this residue of rice LRT2/OsCYP2 and moss PpDGT cause severely impaired auxin signalling 17,30 . Homologous structure modelling based on the crystal structure of wheat (Triticum aestivum) TaCypA-1 (PDB code: 4E1Q) 34 , a cyclophilin sharing 87% identity with LRT2, revealed that Gly 72 is located at the surface of LRT2 immediately adjacent to a b-sheet ( Supplementary Fig.…”
Section: Lrt2 Catalyses Cis/trans Isomerization Of Osiaa11 Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…The unusual FK506-binding domain in TWD1 was instead found to participate in protein interaction with ABCB-type auxin transporters and is apparently involved in the functional regulation of these transporters [44] (see Section 4). TWD1 also possesses a tetratricopeptide repeat domain (common [131] Regulation and PM-to-ER trafficking of ABCB-type auxin transporters [8,9] Z. mais [133] Interaction with ABCB transporters on PM (via FKB-domain) [8,62], ABCC transporters on tonoplast (via TPR domain) [66], with HSP90 (TPR domain) [62,65] and calmodulin (calmodulin-binding domain) [66] Over-expression of TWD1 lacking its membrane anchor results in hypermorphic growth [64] FKBP72/PAS1 A. thaliana [69] Unclear (C-terminal membrane anchor), nuclear [68,134] Low, inhibited by FK506 and rapamycin [134] Up-regulated cell division, leaf fusions, short hypocotyls, sterile [69] O. sativa [131] Chaperon during translocation of NAC-like transcription factor (AtFAN) into nucleus [68] Z. mais [133] Regulation of very long fatty acid elongation [70] -DGT/CypA/ROC1/CYP1/CYP2/ P. patens [10] Nuclear and cytoplasmic [10,90], phloem sieve elements [79] Significant [77,78], inhibited by CsA [78] Regulates growth [90], gene expression [84,90,92], patterned cell division [88], phloem function [79], ROS balance in root apical meristem [87] A. [137] in many large immunophilins) that was shown to interact with vacuolar ABC transporters of the C subclass and HSP90 [65,66], as w...…”
Section: Plant Immunophilins Are Implicated In Regulation Of Developmentmentioning
confidence: 99%
“…2), and can move from shoot to root in grafted plants partially restoring the lack of lateral roots in dgt mutant rootstocks [89]. A DGT-like small cyclophilin from Physcomitrella patens is also important for auxin-regulated growth [90], whereas a related cyclophilin from rice (LATERAL ROOTLESS2, LRT2/OsCYP2) plays a crucial role in auxin-regulated lateral root formation [91] and has been shown to directly regulate the stability of the auxin-responsive transcriptional repressor protein, OsIAA11, via peptidylprolyl isomerization [92]. The Arabidopsis cyclophilin CYCLOPHILIN20-2 regulates flowering time by modulating the conformation of BRASSINAZOLE-RESISTANT1 in Ref.…”
Section: Box 2: Immunophilins In Regulation Of Plant Development and mentioning
confidence: 99%